Anti-corruption as a variable for civil servants’ performance measurement: A systematic literature review - Puspitarini, Rastiana (FIA UB, 2019)
The purpose of this research is to elaborate variables of anti-corruption in the performance measurement in civil servants. This study was conducted by describe and analyze the experience of Great Britain to reduce corruption in the public sector. A systematic leitrature review was conducted to analyse anti-corruption varibales in the civil servant performance measurement. The findings show that two main variables used in the performance measurement: moral revolution and compliance. The finding suggests that the need for integrating moral revolution and compliance in order to optimize the combating of corruption in public sectors.